Towards a compact all-optical terahertz-driven electron source - Xu, Hanxun; Li, Renkai; Yan, Lixin; Du, Yingchao; Tian, Qili; Huang, Wenhui; Tang, Chuanxiang (Frontiers in Physics, 2023)
We propose a physical design of a compact all optical terahertz (THz)-driven electron source. The 300 mm accelerator beamline, powered by Joule level laser system, is easily to be integrated to tabletop scale. A THz-driven electron gun, a tapered dielectric loaded cylindrical waveguide, THzdriven bunch compressors and permanent solenoid magnets (PMS) have been designed and optimized. Dynamics simulations show that the electron source can deliver a 19 fC, 3 MeV electron beams with a normalized transverse emittance of 0.079 π.mm.mrad. A minimum relative energy spread of 0.04% or a minimum root-mean-square bunch length of 6.1 fs can be achieved. Sensitivity analysis shows that the THz-driven electron source can effectively work with laser power jitter within 1.5%. Simulation studies also reveal the potential of the design THz-driven electron source for achieving high quality ultrafast electron diffraction (UED). Prototype THz-driven electron guns have been fabricated and is now under testing, more results will be reported in future works.